2012
DOI: 10.1655/herpetologica-d-10-00058
|View full text |Cite
|
Sign up to set email alerts
|

Water Balance and Spatial Distribution of an Anuran Community from Brazil

Abstract: Terrestrial amphibians may dehydrate when exposed to low humidity, representing an important factor affecting spatial distribution and community composition. In this study we investigated whether rates of dehydration and rehydration are able to explain the spatial distribution of an anuran community in a Restinga environment at the northern coast of the State of Bahia, Brazil, represented by 11 species distributed in 27 sample units. The environmental data set containing 20 variables was reduced to a few synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 37 publications
0
20
0
3
Order By: Relevance
“…Furthermore, some SUs in shrubby vegetation zones had terrestrial tank bromeliads (Figure 2A), plants that retain moisture between their leaves and accumulate water inside the leaf-tank (Freitas et al 2000, Cogliatti-Carvalho 2001. In shrubby vegetation zones, terrestrial tank bromeliads are the only source of water supply to maintain the minimum physiological needs of anurans (Dabés et al 2012) and are considered fundamental ecological units in the Restinga ecosystem since they are used by many wildlife groups for shelter and/or as breeding sites (Peixoto 1995, Richardson 1999, Carvalho-e-Silva et al 2000, Schneider & Teixeira 2001, Teixeira et al 2002. The phytotelm-dweller hylids Phyllodytes melanomystax and Trachycephalus atlas were exclusively observed in these bromeliads, although as singletons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, some SUs in shrubby vegetation zones had terrestrial tank bromeliads (Figure 2A), plants that retain moisture between their leaves and accumulate water inside the leaf-tank (Freitas et al 2000, Cogliatti-Carvalho 2001. In shrubby vegetation zones, terrestrial tank bromeliads are the only source of water supply to maintain the minimum physiological needs of anurans (Dabés et al 2012) and are considered fundamental ecological units in the Restinga ecosystem since they are used by many wildlife groups for shelter and/or as breeding sites (Peixoto 1995, Richardson 1999, Carvalho-e-Silva et al 2000, Schneider & Teixeira 2001, Teixeira et al 2002. The phytotelm-dweller hylids Phyllodytes melanomystax and Trachycephalus atlas were exclusively observed in these bromeliads, although as singletons.…”
Section: Discussionmentioning
confidence: 99%
“…This mode of reproduction allows this species to breed in environments deprived of water bodies (Xavier & Napoli 2011). Furthermore, P. paulodutrai has a low dehydration rate and high rate of rehydration from a neutral substrate (Dabés et al 2012), which helps to explain its ability to occupy different types of environments, including those under high osmotic stress, as is the case of shrubby vegetation zones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species which do not present either physiological or morphological adaptations, to cope with water loss by evapotranspiration, may use behavioral responses as an important mechanism to resist dehydration (Wells, 2007). Among the many water saving behavioral aspects, the following stand out (Stille, 1958): 1) activity period, which is mostly nocturnal for anurans; avoiding high temperatures and low humidity during the day; 2) spatial distribution through habitat and micro-habitat choice, because amphibians that are less tolerant to dehydration are found mostly in regions with elevated humidity or near water bodies (Pough et al, 1977;Bastazini et al, 2007;Xavier and Napoli, 2011;Dabés et al, 2012); 3) aggregation of newly metamorphosed individuals on salamander adults; reducing the exposed surface area when under water stress (Rohr et al, 2002); 4) fossorial habit -occupying holes in the ground dug by other animals or by the amphibians themselves (Shoemaker and Nagy, 1977;Toledo and Jared, 1993;Warburg, 1997;Cartledge et al, 2006;Wells, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on water balance and behavior use anurans from temperate climates, and neotropical anurans may possess specific adaptations (Navas et al, 2004;Dabés et al, 2012). This study focuses on Leptodactylus macrosternum, a semi-aquatic frog found in the tropical region of South America, which like most species of genus Leptodactylus can be found in terrestrial habitats, but needs open water to reproduce (Heyer, 1969), (Heyer and Giaretta, 2009).…”
Section: Introductionmentioning
confidence: 99%